2010
DOI: 10.1021/nl102713c
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Arrays of Single-Layer Graphene Resonators

Abstract: We fabricated large arrays of suspended, single-layer graphene membrane resonators using chemical vapor deposition (CVD) growth followed by patterning and transfer. We measure the resonators using both optical and electrical actuation and detection techniques. We find that the resonators can be modeled as flat membranes under tension, and that clamping the membranes on all sides improves agreement with our model and reduces the variation in frequency between identical resonators. The resonance frequency is tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
220
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(252 citation statements)
references
References 27 publications
17
220
2
Order By: Relevance
“…It is unclear if there remains some polymer residue, although the tensioning trend when cooling has been reported in graphene and several transition metal dichalcogenide membranes. [46][47][48] However, this trend should be explained differently for 2D materials with a negative expansion coefficient like h-BN or graphene, 49 and for that reason we propose an alternative tensioning effect caused by the sidewall adhesion, which should balance out or increase the tension when cooling certain 2D membranes, and explains our results and those on graphene drumheads. Other stronger cleaning routes for h-BN are available, 50,51 although not all of them might be compatible with suspended single-layer structures.…”
Section: Discussionmentioning
confidence: 59%
“…It is unclear if there remains some polymer residue, although the tensioning trend when cooling has been reported in graphene and several transition metal dichalcogenide membranes. [46][47][48] However, this trend should be explained differently for 2D materials with a negative expansion coefficient like h-BN or graphene, 49 and for that reason we propose an alternative tensioning effect caused by the sidewall adhesion, which should balance out or increase the tension when cooling certain 2D membranes, and explains our results and those on graphene drumheads. Other stronger cleaning routes for h-BN are available, 50,51 although not all of them might be compatible with suspended single-layer structures.…”
Section: Discussionmentioning
confidence: 59%
“…Zande et al [96] found that the exponent α=0.35± 0.05 for temperatures below 40 K. For temperatures above 40 K, α = 2.3 ± 0.1. Chen et al [97] observed a similar transition in the Q-factor.…”
Section: Nanomechanical Resonatorsmentioning
confidence: 97%
“…A very high Q-factor has been achieved in the laboratory at low temperatures. Bunch et al observed a Q-factor of 9000 for a graphene nanoresonator at 10 K [96]. Chen et al also found that the Qfactor increased with decreasing temperature, reaching 10 4 at 5 K [97].…”
Section: Nanomechanical Resonatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16] The transduction schemes used so far have been optical, 9,11,12 mechanical, 10 and electric. [13][14][15][16] Because electron transport through mesoscopic graphene devices can be coherent, [17][18][19] using graphene in NEMS means that phase coherent transport phenomena can be directly integrated into NEM resonators. As shown in this paper, this allows the motion of the NEMS to couple to the length scale set by an intrinsic scale, the interatomic distance a 0 ≈ 1.4Å.…”
Section: Introductionmentioning
confidence: 99%